Kontush Sashes from the Northern Crypt of the post-Bernardine Church of the Elevation of the Cross in Łuków (Lublin Province) - Jarosz, Jan; Grupa, Małgorzata (Analecta Archaeologica Ressoviensia, 2022)
An archaeological exploration conducted in 2019 in the crypts of the post-Bernardine church of the Elevation of the Cross in Łuków brought various finds of burial goods, excavated in fragments, probably transferred together with human remains in the 19th century to ossuaries located in the crypt. The artefacts included fragments of three kontush sashes, being the most indispensable and splendid element of the Polish national costume. The analysis of these objects, both in terms of ornamentation and technology, helped us to estimate their probable manufacturing location.